Brooks Range vegetation change from repeat imagery, Alaska, 1970s to 2010s ... - Dial, Roman; Wong, Russell; Wockenfuss, Amy (NSF Arctic Data Center, 2023)
This data set represents 23 study sites across 22 degrees of longitude along treeline in Alaska's Brooks Range. Each study site was approximately 50 square kilometers in area and sampled with approximately n = 3,000, randomly-placed 6 meter (m) diameter disks. Each of the 63,224 disks were classified by humans into coarse vegetation classes twice, once using 1970s aerial orthophotos (e.g., Alaska High-Altitude Photography) and again using 2010s very-high resolution satellite imagery (e.g., MAXAR World-View). In addition, annual maximum Landsat normalized difference vegetation index (NDVI) values were extracted from a subset of these disks (n = 27,835 from 12 study sites) for Theil-Sen regression on greening trends using the R package LandsatTS. ...